Innovation in sodium borohydride production process from borosilicate glass with sodium under hydrogen atmosphere:: high pressure process - Kanturk, Aysel; Piskin, Sabriye (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This paper presents a new process for producing sodium borohydride (NaBH4), which can be used as a hydrogen storage medium. The process is based on the conversion reaction of borosilicate glass at temperatures between about 400 and 500 degrees C under high hydrogen pressure of 22atm. For this purpose, borax (Na2B4O7) is sintered with quartz powder NOD to obtain borosilicate glass then heated with metallic sodium (Na) under high hydrogen pressure. Furthermore, a study of the hydrogenation characteristics of borosilicate glass has been made using change in hydrogen pressure drop as function of reaction time in the process. It is concluded that the required hydrogenation time is 70 min at 475 degrees C under 22 ann of hydrogen pressure for production of NaBH4 with excellent yield. (c) 2007 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium borohydride; borosilicate glass; high pressure; hydrogen storage; CATALYST; Chemistry; Electrochemistry; Energy & Fuels